Inhibition - Koutsomichalis, Marinos (My University, 2026)
Live performance and workshop of the hybrid interactive art project 'Inhibition' at the DA_Fest in the National Academy of Fine Arts in Sofia, BU. https://www.2017.da-fest.bg/en/events-go/inhibition